MODERN PROBLEMS OF PROFILE TRAINING OF SCHOOLS OF SECONDARY SCHOOLS - Yakovlyeva В.А.; Mokryy О.Б. (Pedagogy of Higher and Secondary Education, 2022)
In article the urgency of a problem profile preparation of learning comprehensive schools of boarding schools is proved; the analysis of last researches and publications in which consideration problems is started and on which the author leans (bases) is lead (carried out); the primary goals of profile training and the important directions of high quality maintenance of preparation of the future teachers of labour training are determined: innovative approaches in preparation of the future experts of technologies for profile training learning modern comprehensive schools of boarding schools are considered.